Sosialisasi PHBS Di SDN Pohsangit Leres I Sebagai Strategi Pencegahan Stunting - Irdina Iffata Qottrunnada; Singgih Manggalou; Mohammad Ferry Ariyanto; Anisya Naharuddin; Muhammad Fikri Ardiansyah (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Stunting is a problem in nutrition that is in the spotlight of the world, especially a priority for Indonesia. Stunting is a condition that occurs in the early period of growth and development that occurs in the early period of development that occurs due to nutritional status. stunting can cause problems in children's health so that it interferes with educational productivity. Therefore, an effort is needed to prevent stunting, one of which is by carrying out socialization activities on Clean and Healthy Behavior (PHBS). Provide an understanding related to PHBS that can be instilled early on by conducting socialization on Clean and Healthy Behavior in elementary schools. The purpose of this PHBS socialization is to provide education regarding the importance of PHBS for health so that it is hoped that it can be applied in everyday life. The method used is by giving pre-test andpost-test and provide materials related to PHBS. The material presented begins with an explanation of what is meant by clean and healthy living, the benefits of clean and healthy living, why it is necessary to practice clean and healthy living behaviors and what needs to be done for a clean and healthy life.Pre-test andpost-test which is to measure students' understanding of PHBS before and after teaching the material. The results of this socialization were an increase in understanding of Clean and Healthy Behavior at SDN Pohsangit Leres I before the socialization touched 44.83% to 88.33%.